Atmospheric Volatile Organic Compounds and Ozone Creation Potential in an Urban Center of Southern Nigeria. (21st August 2014) - Olumayede, Emmanuel Gbenga
Abstract : The relative contribution of individual volatile organic compounds (VOC) species to photochemical ozone formation depends on their atmospheric concentrations and their oxidation mechanism. In an attempt to evaluate the ozone creation potential of ambient VOCs captured in an urban settlement of Benin City, Nigeria, the VOCs concentrations data collected in field studies at nine measurement sites of different air quality in the city and a background site were analysed. Air samples were collected at human breathing height of 1.5 meters from ground level at each site. Active sampling method using the low volume sampling pump (Acuro, Drager, Lubeck, Germany) was used to drawn the air into the tube; the absorbent was Chromosorb 106. The sampling periods were between May 2010 and June 2011; the period covered both dry and wet seasons. The adsorbed gases were desorbed using solvent extraction method with carbon disulphide as solvent. The extracted solutions were analyzed with gas chromatography and mass spectrometer. The observed concentrations of individual VOCs were determined and maximum incremental reactivity (MIR) coefficient along with rate constants of VOC-OH reactions were applied to assess the ozone formation potential of individual VOC in the ambient atmosphere. Sixteen VOC species were observed at various sites with mixing height in decreasing order: toluene (5.82), mp-xylene (3.58), ethylbenzene (3.46), benzene (2.29), and n-butane (0.84). The ozone formation potential study revealed that, ranking by propyl-equivalent, the alkanes included in this study account for 58% of the total propyl-equivalent concentration. The total ozone creation potential in the atmosphere of the Benin City was calculated to be 281.1 µ g/m 3 . A comparison of total ozone formation potential (OFP) in our study with results obtained from other cities of the world revealed that the total concentration of ozone production in our study is threefold lower than the values reported in China city of Foshan. It is suggested that the sources of this pollutant need to be monitored in the area as a way of curtailing the impact of ozone in this city.